Efecto del estrés abiótico sobre la síntesis y degradación del almidón. Una revisión - Tofiño Rivera, Adriana Patricia; Romero, HM; Ceballos, H. (2007)
In higher plants, starch biosynthesis is highly sensitive to stress acting on the supply of carbohydrates from source organs, sink activity, and the activities of associated enzymes. Whole plant measurements in vivo have demonstrated that carbon flow rates are additionally dependent on the properties of sink, as well as those of whole transport system. In this article, some issues of the adjustment of this interaction through the complex of cellular responses to abiotic stress are reviewed. The aspects of pathway of stress signaling and its influence on the genetic program of starch expression are also elucidated. Additionally, the pathway, by which a plant senses and responds to environmental cues and endogenous signals through changes in carbon partitioning and increases in soluble sugar cell concentration, and other adaptive physiological strategies are considered.